1965
DOI: 10.1071/bi9651103
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis in Artificial Communities of Cotton Plants in Relation to Leaf Area I. Experiments with Progressive Defoliation of Mature Plants

Abstract: SummaryThe relation between the leaf area index (L.A.I.) of artificial communities of cotton plants and their rates of dark respiration and of net photosynthesis at three light intensities was examined. The L.A.I. was varied by the removal of successive layers of leaves, working from the base of the canopy upwards. Experiments were carried out at 20, 30, and 40°0 to vary the relative magnitudes of respiration and photosynthesis.At all temperatures and light intensities, net photosynthesis by the communities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

1966
1966
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 5 publications
1
37
0
1
Order By: Relevance
“…Subsequent work with communities of corn (Williams, Loomis, and Lepley 1965), soybean (Shibles and Weber 1965), and lucerne (Wilfong, Brown, and Blaser 1967) plants showed no decline in net photosynthesis or crop growth rate at high L. A.I. values. This finding is in agreement with our earlier work (Ludwig, Saeki, and Evans 1965) with communities of mature cotton and sunflower plants. In these it was shown that the lack of a decline in net photosynthesis by the communities at high L.A.I.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Subsequent work with communities of corn (Williams, Loomis, and Lepley 1965), soybean (Shibles and Weber 1965), and lucerne (Wilfong, Brown, and Blaser 1967) plants showed no decline in net photosynthesis or crop growth rate at high L. A.I. values. This finding is in agreement with our earlier work (Ludwig, Saeki, and Evans 1965) with communities of mature cotton and sunflower plants. In these it was shown that the lack of a decline in net photosynthesis by the communities at high L.A.I.…”
Section: Introductionsupporting
confidence: 83%
“…The methods used for the measurement of CO2 and water vapour levels, air and leaf temperatures, and light intensities have been described in detail by Ludwig, Saeki, and Evans (1965). In the present experiments the fresh air supply to the cabinets was drawn directly from the atmosphere by way of a pipe of 15 cm diameter, in which the air flow was adjusted with a baffle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other plants for which no optima in net photosynthesis rates have been found under controlled conditions are kale (17), wheat, rice, sunflower, and perilla (25), and cotton (12). Ludwig, Saeki and Evans (12) showed by progressive defoliation that the lower leaves of a cotton commuinity had low rates of respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Ludwig, Saeki and Evans (12) showed by progressive defoliation that the lower leaves of a cotton commuinity had low rates of respiration.…”
Section: Discussionmentioning
confidence: 99%